Impact of Beijing-Guangzhou High-speed Rail on Capital Accumulation in Cities Along the Line. (January 2020) - Cheng, Qianwen
Abstract: The development of transportation has triggered regional element flows by changing the location conditions of cities along the route. In recent years, with the full implementation of the National Medium and Long-term Railway Network Plan, China's high-speed railway network layout has continued to expand, and high-speed rail has become an important means of transportation for people. The development of high-speed railways will definitely have a wide-ranging and far-reaching impact on the concentration of elements along the route. This article takes the Beijing-Guangzhou high-speed rail as an example, adopts the matching idea as the high-speed rail experimental group to match the control group, and estimates the impact of high-speed rail on the accumulation of capital factors by constructing a double difference model. The results show that the completion of the Beijing-Guangzhou high-speed rail has made a significant contribution to capital agglomeration.